1989
DOI: 10.1161/01.res.65.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Response of isolated working hearts to fatty acids and carnitine palmitoyltransferase I inhibition during reduction of coronary flow in acutely and chronically diabetic rats.

Abstract: The effects of palmitate on mechanical failure of ischemic hearts were studied in acutely (48-hour) and chronically (6-week) streptozotocin diabetic rats. Coronary flow was reduced by 50% in isolated working hearts perfused at a 15 cm H2O preload and 100 mm Hg afterload by the one-way ball valve model of ischemia. Peak systolic pressure (PSP) and cardiac output (CO) decreased 40% by 4 minutes in control hearts perfused with 11 mM glucose and paced at 280 beats/min, compared with 50% in hearts from acutely diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 28 publications
4
41
0
1
Order By: Relevance
“…Transgenic mice with increased cardiac uptake of fatty acids due to overexpression of long-chain acyl-CoA synthetase develop cardiomyopathy (20). Studies performed with isolated working hearts of diabetic animals have demonstrated that high rates of FAO are associated with ventricular dysfunction (4,5,21). Recently, we have shown that chronic activation of the PPAR␣ pathway (MHC-PPAR mice) leads to a marked increase in myocardial fatty acid uptake and oxidation, reduced glucose utilization, and cardiomyopathy, a metabolic and functional phenotype similar to that of the diabetic heart (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mice with increased cardiac uptake of fatty acids due to overexpression of long-chain acyl-CoA synthetase develop cardiomyopathy (20). Studies performed with isolated working hearts of diabetic animals have demonstrated that high rates of FAO are associated with ventricular dysfunction (4,5,21). Recently, we have shown that chronic activation of the PPAR␣ pathway (MHC-PPAR mice) leads to a marked increase in myocardial fatty acid uptake and oxidation, reduced glucose utilization, and cardiomyopathy, a metabolic and functional phenotype similar to that of the diabetic heart (6).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas mitochondrial fatty acid oxidation (FAO) is the chief energy source for the normal postnatal mammalian heart, the relative contribution of glucose utilization pathways is significant, allowing the plasticity necessary for steady ATP production in the context of diverse physiologic and dietary conditions (3). Because of the importance of insulin in the regulation of myocardial metabolism, chronic insulin deficiency or resistance results in a marked reduction in cardiac glucose utilization such that the heart relies almost exclusively on fatty acids to generate energy (4,5). High rates of fatty acid utilization in the diabetic heart could lead to functional derangements related to accumulation of lipid intermediates, mitochondrial or peroxisomal generation of reactive oxygen species, or excessive oxygen consumption.…”
mentioning
confidence: 99%
“…Similarly, a recent study (214) has shown that the hypertrophied heart is characterized by a marked shift in substrate preference from typical fatty acid to primarily glucose metabolism, which is more readily converted to ATP. However, in conditions of insulin resistance, glucose metabolism is impaired, and the heart is forced to revert to fatty acid and ketone catabolism (146), resulting in structural and other biochemical changes that ultimately lead to left ventricular hypertrophy and diastolic (impaired relaxation) and systolic dysfunction (10, 79,111,137,147,160,212). In fact, a study (209) in humans has demonstrated that short-term depletion of serum free fatty acids in failing hearts results in impaired cardiac work as the heart typically responds to decreases in free fatty acids by increasing glucose metabolism.…”
Section: Myocardial Metabolic Signalingmentioning
confidence: 99%
“…[15][16][17][18][19][20] In addition, reduced capacity for glucose oxidation has also been linked to ventricular dysfunction, especially in the ischemic and postischemic heart. 13,14,[21][22][23] The metabolic reprogramming of the diabetic heart is driven, in part, by gene-regulatory events. Coordinate activation of genes involved in cellular FA uptake and utilization pathways in the diabetic heart has been shown to occur via the transcription factor peroxisome proliferator-activated receptor ␣ (PPAR␣).…”
mentioning
confidence: 99%